ASSOCIATION OF CHILDHOOD PHYSICAL EXAMINATION AND LABORATORY PARAMETERS WITH HIGH BLOOD PRESSURE IN JAPANESE YOUNG ADULTS. (April 2021) - Azegami, Tatsuhiko; Uchida, Keiko; Arima, Fujiyo; Sato, Yasunori; Awazu, Midori; Inokuchi, Mikako; Takeda, Ayano; Itoh, Hiroshi; Tokumura, Mitsuaki; Mori, Masaaki
Abstract : Objective: We aimed to identify childhood risk factors for high blood pressure (BP) in young adults. Design and method: Childhood data were obtained from medical checkups of Japanese male and female junior high school students aged 12-13 years during the period from 2008 to 2009. Childhood variables were sex, body weight, body mass index (BMI), systolic BP, complete blood count, uric acid, total cholesterol, high density lipoprotein cholesterol, and low density lipoprotein cholesterol. The 1129 participants were followed up for average 8.6 years with a range of 6.0 to 9.0 years. High BP was defined as elevated BP and hypertension of ACC/AHA BP category (systolic BP 120 mmHg or more and/or diastolic BP 80 mmHg or more). Results: At the follow-up, the prevalence of high BP was 42.2% in male young adults and 7.7% in female young adults. The mean systolic/diastolic BP was 117.8 [SD, 10.1] / 63.6 [SD, 6.1] mmHg in men and 105.2 [SD, 9.6] / 59.6 [SD, 5.5] mmHg in women. Univariable logistic regression analysis showed that systolic BP (odds ratio 1.56), body weight (1.50), uric acid (1.38), and red blood cell (1.31) at childhood baseline were significantly associated with high BP in male young adult, whereas variables associated with high BP were not found in female young adults because few women developed high BP. A logistic regression analysis with the stepwise method indicated that the regression model including systolic BP, body weight, WBC, platelet count, and uric acid had a high prediction power for high BP in male young adults (Area under curve 0.660, p < 0.001). Conclusions: These results suggest that childhood medical checkup information including BP, anthropometric data, and laboratory parameter can contribute to the prediction of future high BP in young adults.